Study on the Development of Religious Tourism in Banjarmasin in the New Normal Era (Journal of Wetlands Environmental Management, 2024)
The city of Banjarmasin has the potential for religious tourism, especially tourism objects in the form of the tombs of the Ulama (Habib) and old mosques that have Islamic historical value in Bumi Lambung Mangkurat, including the Sultan Suriansyah Mosque, Sultan Suriansyah's Tomb, Surgi Mufti's Tomb, Al Allamah Datu Muhammad Amin's Tomb (Habib Datu Amin or Habib Benua Anyar), Tomb of Al Habib Hamid bin Abbas Bahasyim (Habib Basirih), and Tomb of Habib Abu Bakar Bin Salim Al Habsyi (Habib Basirih). This study aims to 1) explore the potential and obstacles faced by religious tourism objects from the historical, physical, and socio-cultural aspects of the surrounding community, and 2) analyze the development of religious tourism objects in Banjarmasin City. This research is a qualitative descriptive study describing the object of research in the form of Islamic religious tourism in Banjarmasin City along with the potential and obstacles faced, which are expected to be further developed as an integrated pilgrimage tourism destination. The results of the study indicate that the constraints that exist in religious tourism objects are related to the lack of availability of facilities and infrastructure and their maintenance, the weak ability of local resources in developing and marketing various products that can be sold around religious tourism objects, and the weakness of promotional programs. The development that can be done is by running an appropriate marketing program for religious tourism objects; proper promotion and positioning of religious tourism objects as pilgrimage tourism, improving infrastructure, facilities, and infrastructure, and establishing cooperation between the government, managers, and the community in maintaining and maintaining the sustainability of religious tourism objects in Banjarmasin.